The Effect of Emotional Intelligence and Leadership of Principal Towards Teacher Performance of Vacational School With Motivation As Moderating Variable. - Setyowati, Diah Riany; Joko Rharjo, Tri; Budi Utomo, Cahyo (Educational Management, 2019)
The existence and success of an organization in achieving its goals, can not be separated from the human resources factor. The purpose of this study to determine the effect of Emotional Intelligence and Leadership Principal of the Private Vocational Teachers performance with motivation as variable Moderation. This type of research that is explanatory research, data collection techniques were questionnaires and interviews. The sample in this study amounted to 250 respondents technique is proportional random sampling, measurement scale using a Likert scale. Quantitative analysis using validity, reliability test, the coefficient of correlation, simple and multiple regression analysis, the coefficient of determination, significance test (t test and f) and path analysis (path analysis). Based on the research results show that emotional intelligence (X1) and leadership (X2) either simultaneously or partially affect the work motivation (Y1) and the performance of teachers (Y2). Based on the results of the path analysis, the direct effect of emotional intelligence and leadership on teacher performance is greater than the indirect effect through work motivation. Based on these results, it is recommended that schools can improve the performance of teachers including the improvement of work motivation of teachers and the provision of rewards to teachers in the form of flattery directly from employers so that employees are proud of the work that has been done so as to encourage the teachers to work more optimally and improve communication between teachers and leaders.